Nablus Municipality Redesign - Tubeileh, Nour Aldin (My University, 2018)
The project included an integrated redesign of the Municipality of Nablus City, located on Faisal Street, with an total area of 556 m2, in terms of architectural and construction and environmental aspects, as the current building lacks a functional distribution that suits the scope of the work of the building. Architectural design were designed to suit the functional nature, and the use of lighting and sound systems in accordance with the functions according to international standards and standards, and the development of central systems such as heating system and air conditioning, and fire suppression system. The new design included 11 floors, as well as the old design, which contains only 5 floors, so the facilities were distributed in areas commensurate with the nature of work, and was added to the internal parking of municipal employees